Correlation between microstructures and mechanical properties of high-speed friction stir welded aluminum hollow extrusions subjected to axial forces. Issue 1 (January 2018) - Liu, Xiangqian; Liu, Huijie; Wang, Tianhao; Wang, Xiangguo; Yang, Si
Abstract: The AA6005A-T6 aluminum hollow extrusions were friction stir welded at a high welding speed of 2000 mm/min and various axial forces. The results show that the nugget zone (NZ) is characterized by fine equiaxed grains, in which a low density of equilibrium phase β is observed. The grains in the thermo-mechanically affected zone (TMAZ) are elongated, and the highest density of dislocations and a low density of β' precipitates can be found in grains. The heat affected zone (HAZ) only experiences a low thermal cycle, and a high density of β" precipitates and a low density of β' precipitates remain in the coarsened grains. The microhardness evolutions in the NZ, TMAZ and HAZ are governed by the grain refinement and dislocation strengthening, the dislocation and precipitation strengthening, and the precipitation and solid solution strengthening, respectively. When increasing the axial force, the changing trend of one strengthening mechanism is contrary to the other in each zone, and the microhardness increases in different zones. As a result, the tensile strength roughly increases with raising the axial force, and all joints show good tensile properties as the high welding speed inhibits the coarsening and dissolution of strengthening precipitates significantly.